Uwagi na temat dopuszczalności analogicznego stosowania przepisów o darowiźnie do umowy przekazania nieruchomości - Krupowicz, Bartłomiej (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
In 2008, the derogated article 179 of the Polish Civil Code was replaced by a new type of contract, namely real estate transfer contract. Until now, the contract was not a subject of wider interest of civil law doctrine and judicature. Its short regulation considering some functional and systematic arguments implies that it is not fully regulated in the Title XXXIII1 of the Civil Code and it is possible to analogically use for it some institutions characteristic for the endowment contract. In the present article the author discusses the arguments which have appeared in doctrine until now, according to which such an analogy is forbidden and points to the area of endowment contract regulations which can be also compared to real estate transfer.
Keywords: endowment contract; real estate transfer contract; analogy; obligations